Implementation Of Zoning System Policy On Admission Of New Student Participants (Ppdb) Junior High School In Singkawang City (Study At The Singkawang City Education And Culture Service 2023-2024) - Zuliyantini, Zuliyantini; Nandang, Nandang; Sagita, Novie Indrawati (UNIVERSITAS PAKUAN, 2025)
The implementation of the SMPN PPDB zoning system policy in Singkawang City is inseparable from various challenges and obstacles. Some of the problems that arise include: the uneven distribution of junior high schools in all sub-districts, the limited capacity of school capacity, the gap in quality and facilities between schools, and the community's understanding of the zoning system which is still diverse. Through the Regulation of the Mayor of Singkawang City Number 26 of 2023 regulates the implementation of new student admissions (PPDB) for the 2023/2024 school year. In this regulation, the zoning system remains one of the main channels, namely through zoning at least 50% of the total capacity of junior high schools in Singkawang City. The purpose of this research is to find out the Implementation of the Zoning System Policy on the Admission of New Learners (PPDB) of SMPN in Singkawang City and to find out the factors that hinder the Implementation of the Zoning System Policy by using 3 aspects of Mazmanian Sabatier's theory as material for the implementation of the zoning system policy at the junior high school level in Singkawang City. This research method uses descriptive qualitative methods. Data collection was carried out by interview, observation and documentation with the determination of informants using purposive techniques. The results showed that the implementation of the zoning system policy on PPDB at SMP Negeri 3 Singkawang showed significant progress both from the aspects of problem characteristics, policy characteristics and the policy environment, One of the main objectives of the zoning system is to create equal access to education and eliminate the predicate of favorite schools. However, there are technical obstacles such as validation of domicile data that is often inaccurate. This suggests the need for stricter supervision and a more effective verification system to ensure the accuracy of the data used in the enrollment process. The author therefore suggests that the Singkawang City Education and Culture Office needs to form a verification team involving the local community (RT/RW) to ensure the accuracy of student domicile data. This can reduce the potential for address forgery and increase public trust in the zoning system.